Traction of a superior central incisive in ectopic position with a modified hawley: a clinical case report. - Sánchez-Achío, Tony (2022)
The prevalence of impaction of the permanent maxillary incisors ranges from 0.06 to 1% of the population. One of the possible causes of impaction of the upper central incisor is the presence of an odontoma. The objective of this clinical case study was to propose an orthodontic treatment proposal for a girl with early mixed dentition, pulling an impacted maxillary central incisor, a rare problem in the population, caused by the presence of a compound odontoma. A 6- year-old and 2-month-old female patient presented to the private consultation. On clinical examination, she showed a delay in exfoliation of the teeth 5.1 and 5.2, the panoramic radiograph revealed the presence of a compound odontoma. And in the tomography, the dental piece 1.1 was observed in an ectopic position, horizontal in the sagittal plane. The composite odontoma was removed at the same time as the retained tooth was exposed, and it was decided to use a modified Hawley, type removable appliance with a tower to perform traction of the tooth. The choice of good diagnosis of bone pathologies and dental alterations. The patient presented an impaction of tooth 1.1 and due to her early mixed dentition, it was not possible to treat it conventionally with fixed bracket appliances, reason why it was decided to make a modified Hawley type removable appliance. The treatment time for dental traction was 8 months, a relatively short time, according to the literature.